THE EFFECT OF SERVICE QUALITY, SOCIAL MEDIA, AND ONLINE TRAVEL AGENTS ON CUSTOMER SATISFACTION WITH CUSTOMER TRUST AS A MEDIATING VARIABLE AT GRAND ELITE HOTEL PEKANBARU - Rasmonowati, Henni; N, Arizal; Soviyanti, Efrita (Jurnal Daya Saing, 2026)
This study examines the effect of service quality, social media, and online travel agents on customer satisfaction, with customer trust as a mediator at Grand Elite Hotel Pekanbaru. Amid intense competition and digital transformation in hospitality, hotels must enhance service and digital engagement to sustain satisfaction and trust. Using PLS-SEM quantitative approach, data from 355 valid guest questionnaires were analyzed via SmartPLS. Reliability/validity tests confirmed indicator loadings, AVE, and composite reliability. Structural assessment via path coefficients, R-square, and bootstrapping showed service quality, social media, and OTAs positively impact trust and satisfaction. Trust partially mediates these relationships. Findings enrich hospitality literature by linking service quality, digital marketing, and trust mediation. Practically, managers should boost service performance, social media interaction, and OTA reliability to elevate satisfaction.